Psychiatric assessment of mood instability: qualitative study of patient experience. - Bilderbeck, A; Saunders, K; Price, J; Goodwin, G (Royal College of Psychiatrists, 2014)
BACKGROUND: Mood instability is a common reason for psychiatric referral. Very little is known about how patients with unstable mood experience assessment and diagnosis. AIMS: To investigate the experiences of assessment and diagnosis among patients with mood instability and to suggest improvements to this process. METHOD: Qualitative study, gathering data through individual interviews with 28 people experiencing mood instability and receiving a psychiatric assessment in secondary care. RESULTS: Participants described the importance of receiving an explanation for their symptoms; the value of a good interpersonal relationship with their clinician(s); being listened to and acknowledged; and being involved in and informed about clinical decisions. These needs were not, however, consistently met. Receiving a psychiatric diagnosis, including a diagnosis of bipolar disorder or borderline personality disorder, evoked both positive and negative responses among participants, relating to stigma, personal understanding and responsibility, prognosis and treatment. CONCLUSIONS: Patients with mood instability seek explanation for their symptoms and difficulties, empathetic care and consistent support as much as cure. Clinicians may incorrectly assume what patients' attitudes towards diagnosis are, a mismatch which may hamper the development of a strong therapeutic relationship. Clear, patient-centred communication, which acknowledges the patient's experience, may result in greater patient engagement and satisfaction.